Growth strategy as practice in small firm as knowledge structure. (31st January 2006) - Bellini, Emilio; Lo Storto, Corrado
In this explorative research, based on a study of 80 Information and Communication Technology Small Firms (ICT SFs), a framework to inquire into strategic management of SFs is proposed, moving from the idea that a more coherent and careful conceptualisation of relationships between the firms' growth strategies, and their knowing process is operationalisable. A 'strategy as practice' approach is proposed to deal with some open problems both in theoretical and empirical studies related to specific issues of SFs' strategies, capabilities, and processes, and a model of 'small firm as knowledge structure' is defined. Results coming from the empirical research indicate that the knowledge structure profile affects the growth strategy performance of the firm, while the Entrepreneurial and Management Group (EMG) faces severe limitations to design an effective knowledge structure. Data analysis also suggests some guidelines for policy makers involved in local development of areas with a strong potential of ICT SFs.